Primiparous Adaptation with Postpartum Health Issues in Jeddah City, Kingdom of Saudi Arabia: A Quantitative Study. - Al-Zahrani, Ahlam; Almutairi, Wedad; Elsaba, Howaida; Alzahrani, Sanaa; Alzahrani, Shouq; Althobaiti, Linah; Turkestani, Ohoud (Nursing Reports, 2021)
Background: The postpartum or puerperium period is the first 6 weeks after giving birth to an infant. The postpartum period can have negative implications, especially in first-time mothers. With their transition into motherhood, new mothers adopt new lifestyles, which can affect their physical wellbeing. Childbirth has physical, psychological, and emotional effects on women as they try to adapt to their new roles in order to get through this period with no or minimal health issues. Study Aim: The current study aims to explore primiparous adaptations with postpartum health issues in Jeddah City at Kingdom of Saudi Arabia. Methods: The research design is quantitative cross-sectional. A structured questionnaire was developed to collect data in relation to depression and weight gain, which consider the most common postpartum health issues. The inclusion criteria of the participants are: primipara, 2 to 6 months postpartum, and living in Jeddah. Results: 140 participants were included in the study. Mothers gained approximately 9.2 kg within the fifth to ninth month after giving birth. Discussion: Postpartum weight retention is a primary challenge in the majority of primiparous mothers and results in reduced quality of life. Nurses were always available to answer questions related to the postpartum health issues and explained the expectations to the family members. Conclusions: Childbirth and the postpartum period for first-time mothers are crucial in their lives as they try to adapt to a new way of life. The postpartum period can have negative implications, especially in first-time mothers. With their transition into motherhood, new mothers adopt new lifestyles, which can affect their physical wellbeing. More research is needed to explore the impact of postpartum health issues in Saudi Arabia.